The Growth Of GaN-Based Low Dimensional Structures By CVD Using Platinum And Palladium Catalysts - Lay Kim, Tan (2019)
This research project presents the growth of low dimensional GaN structures employing monometallic catalyst (Pt and Pd) and bimetallic catalysts (Pd/Pt) by means of chemical vapor deposition based on vapor-liquid-solid mechanism.